Celso Furtado e o plano trienal - a teoria do subdesenvolvimento e as reformas de base - Cabral, Fabio Luis (2010)
This study aimed to highlight the interest in the analysis of the Plano Trienal´s proposals, elaborated by Celso Furtado while Plan Minister of João Goulart´s government. The plan is understood in this study as a result of the underdevelopment theory elaborated by Celso Furtado in his seminal work between the decades of 1950 and 1960, like a Economia Brasileira (1954), Perspectiva da Economia Brasileira (1958) A Pré-Revolução Brasileira (1962) and Dialética do Desenvolvimento (1964), and of his proposal of a development model guided on social justice and democracy defense. The Base Reforms would be, this way, as an adjustment of the past (anachronistic structures, economic or political, that stop the pass to development in the period) as a proposal to the future, to mold the characteristics of a society and economy out of the structural limits of the underdevelopment.